The relationship between college students’ Suicidal ideation and rejection sensitivity: a network analysis - Yang He; Tianqi Yang; Chunyan He; Yuanbei Zhang; Huilin Yang; Shen Huang; Jianjun Liu; Xihong Li; Tao Xu; Shengjun Wu (BMC Public Health)
Abstract Background Rejection sensitivity has a controversial impact on suicidal ideation. However, previous studies have always assessed the relationship between rejection sensitivity and suicidal ideation as a whole based on total scores, which has obscured the fine-grained relationship between them. Objectives The present study aims to investigate the fine-grained relationship between rejection sensitivity and suicidal ideation in college students based on network analysis, and to provide a theoretical basis for identifying potential targets for psychological intervention on suicidal ideation. Methods A total of 663 Chinese college students aged 19–28 years from Xian were investigated in an online study. The Tendency to Expect Rejection Scale (TTERS) and Self-rating Idea of Suicide Scale (SIOSS) were selected to investigate rejection sensitivity and suicidal ideation. Rejection sensitivity and suicidal ideation networks were constructed using R4.1.1 software to examine the links between the dimensions and to calculate the bridge expected influence (BEI) of each node. Results The prevalence of suicidal ideation among college students was 5.6%. The rejection sensitivity and suicide ideation network contained 23 cross-community edges, with the strongest one being the connection between S3 “Despair” and R17 “No confidence”. Within the suicidal ideation community, S3 “Despair” had the highest positive BEI value (0.50). In the rejection sensitivity community, R17 “No confidence” exhibited the highest positive BEI value (0.26), whereas R13 “Sense of collectivity” had the highest negative BEI value (-0.08). Conclusions Complex correlation pathways exist between rejection sensitivity and suicidal ideation. The bridge centrality indicators identified in this study serve as guides for relevant personnel to implement targeted interventions, thereby effectively preventing and mitigating the emergence and persistence of suicidal ideation among college students.